Komunikasi Pembangunan Desa Kemiren Kabupaten Banyuwangi Sebagai Desa Wisata Budaya (The Commercium, 2022)
This study was conducted to describe the development communication of Kemiren Village, Banyuwangi Regency as a Cultural Tourism Village (Study in Kemiren Tourism Village, Glagah District, Banyuwangi Regency) which includes the Central, Regional, and Village Governments. This study also described how communication was built in the Governments’ efforts with the community in carrying out development communication to develop the Kemiren Traditional Tourism Village. This study used qualitative approach that seeks data through primary and secondary data sources by conducting observation and in-depth interviews with Kemiren villagers. In the communication of Kemiren Village Development, Banyuwangi Regency as a Cultural Tourism Village there were 3 forms of the concept of development communication efforts that are formed including: (1). CBT (Community Based Tourism) Strategy in Tourism Village Development Efforts (2). Two-way communication in participatory development efforts (3). Interpersonal communication between Pokdarwis and village communities. With the formation of the development communication of the kemiren village, it can be concluded that the pattern of communication between the Government and the Community.